Toast. The story of a boy's hunger - Slater N. Nigel (London, Harper Perennial, 2004)
This is Nigel Slater`s truly extraordinary story of his childhood remembered through food. Nigel`s likes and dislikes, aversions and sweet-toothed weaknesses form a fascinating and often amusing backdrop to this incredibly moving and evocative memoir of childhood, adolescence and sexual awakening.